AGE, EDUCATION AND CONSUMPTION OF MEDICAL CARE: EVIDENCE FROM MALAYSIA - Cheah, Yong Kang; Azira ABDUL ADZIS; Juhaida ABU BAKAR; Chor Foon TANG; Hock Kuang LIM; Chee Cheong KEE (Malaysian Journal of Public Health Medicine, 2020)
The present study examines age and education determinants of consumption of medical care using Malaysian data. The present study offers a better understanding of the effects of age and education on medical care and assists policy makers in developing more effective intervention measures to improve population health. A nationally representative data with a large sample size (n = 14838) was used for analyses. Several important findings are noteworthy. First, age and education are positively associated with consumption of medical care. Second, the impact of education on medical care varies across age. Third, there is no diminishing marginal effect of education on medical care. Findings of the present study suggest that age and education play an important role in determining consumption of medical care. When designing policies to improve population health, consideration should be given to the effects of age and education factors on consumption of medical care. It is important for policy makers to understand which age group and education level of people are more or less likely to use medical care.